Absolute measurement of photon flux using ionization chamber in (6~20) keV synchrotron radiation X‐rays. (3rd April 2020) - Guo, Siming; Wang, Peiwei; Wang, Ji; Li, Fan; Wu, Jinjie; Zhang, Jian
Abstract : Absolute measurement of photon flux under high‐fluence rate X‐rays was required in photon diagnostics for X‐ray lasers. A free‐air ionization chamber used for the reproducibility of air‐kerma in high‐fluence rate X‐ray was designed, and the monoenergetic X‐rays flux of (6–20) keV were absolutely measured on Beijing Synchrotron Radiation Facility. The energy spectrum of the monoenergetic X‐rays was measured using a silicon drift detector, and the proportion of higher harmonics was determined. The saturation curve, air attenuation correction factor, and composite loss correction factor of the free‐air ionization chamber were obtained experimentally. The air‐kerma rate for the (6~20) keV monoenergetic X‐ray was measured accurately, and the relative combined standard uncertainty of the air‐kerma is 0.61%.